On commutativity in prime Γ-near-rings with symmetric bi-derivations - Dey, Kalyan Kumar; Paul, Akhil Chandra; Sattarovich, Rakhimov Isamiddin (Academic Publications, 2014)
In this paper, we investigate the conditions of a prime Γ-near-ring to be commutative by means of symmetric bi-derivations. We prove that under certain conditions, prime Γ-near-rings will be the commutative Γ rings.